Determination of predominate Leptospira serovars circulating among rat populations in Kuala Lumpur - Al Kattan, Ghada; Bahaman, Abdul Rani; Bejo, Siti Khairani; Mutalib, Abdul Rahim; Zakaria, Zunita (Veterinary Association Malaysia, 2017)
Leptospirosis is re-emerging in Malaysia and many other tropical countries. Its infection of human and animal’s worldwide. The study was carried out to identify predominate Leptospira serovars within rat populations in Kuala Lumpur (KL) by microscopic agglutination test (MAT). As well to investigate the frequency of infection by polymerase chain reaction assays (PCR). The isolated cultures that obtained from culturing kidney tissue of 112 trapped rats from four sites in KL, were identified by MAT using panel of 16 standard hyper immune anti-sera. Besides, identification of Leptospira strains by PCR amplification with G1/G2 and ompL1 Borgpetersenii genes. Results from typing by MAT revealed that 8/57 (7.1%) of cultured isolates reacted against; hyper-immune antisera of serogroup Javanica and 13/57 (22.8%) against serogroup Bataviae. Whereas, the rest of isolates recorded across reactivity 1/20 against serogroups; Icterohaemorrhagiae 2/57, Canicola 1/57, Australis 2/57. From PCR-G1/G2; 50/112 (50.9%) cultures were positive included (40/57 cultures positive to isolation and 10/55 cultures negative to isolation). While, from PCR-ompL1 Borgpetersenii gene; 21/112 (18.7%) cultures positive included (17/57 cultures positive to isolation and 4/55 cultures were negative to isolation). It is obvious from this study that serogroups Javanica and Bataviae were the predominant among rat populations in KL. Also it revealed the high frequency of pathogenic strains among rat populations and their potential risk of humans and animals contracting infection.